The economic benefits of higher education: from high school to labor market - Silveira, Priscilla Bacalhau Velloso da (2018)
Attaining tertiary education has noteworthy implications for both individuals and society. This thesis is composed of three essays related to Economics of Education. The first chapter investigates whether the informational barriers prevent young students from completing high school and starting higher education, by performing an evaluation of a corporate volunteer program that aims to inform students about the benefits of finishing this level of education. The second chapter estimates the returns to college quality and to individual abilities on early career outcomes in Brazil. A new measure of the signal for college quality is proposed for these estimates. The third and last chapter performs a cost-effectiveness analysis of the public provision of higher education compared to private provision in Brazil.